PENGARUH KEBIJAKAN MANAJEMEN KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI DI BEI TAHUN. 2011-2014 - SUYAMTO SUYAMTO (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2015)
The purpose of this study were as follows: (1) Determine the influence investment decisions, financing decisions and dividend policy simultaneously on company value of the manufacturing consumer goods in the Indonesia Stock Exchange the period 2011 - 2014. (2) Determine the influence investment decisions, financing decisions and dividend policy partially on company value of the manufacturing consumer goods in Indonesia Stock Exchange period 2011-2014. This research was conducted on manufacturing companies listed in Indonesia Stock Exchange. The population in this study are all companies manufacturing food and beverage industry sector totaling 35 companies. Then take a sample of companies with purposive random sampling method. Formulation of the problem in this research were: (1) Is there any influence investment decisions, financing decisions and dividend policy simultaneously on company value of the manufacturing consumer goods in the Indonesia Stock Exchange period 2011 - 2014. (2) Is there any influence investment decisions, financing decisions and dividend policy partially on company value of manufacturing consumer goods in Indonesia Stock Exchange period 2011-2014. The final conclusion there is a positive and significant impact either partially or simultaneously investment decisions, financing decisions and dividend policy on company value. The ompany value manufacturing consumer goods in the Indonesia Stock Exchange year period 2011 to 2014 can be explained by the investment decisions, financing decisions and dividend policy of 81,80%, while the remaining 19,20%Â is explained by other factors beyond the study models.